Ultrasonic Analysis of Artificial Cementation Effects on Tropical Clay Soils - Pereira, Géssica Soares; Pitanga, Heraldo Nunes; Ferraz, Roberto Lopes; Rodrigues, Roger Augusto [UNESP]; da Silva, Taciano Oliveira; Nalon, Gustavo Henrique (Springer Nature, 2024)
Soil–cement mixtures have practical applications in geotechnical engineering. Peculiarities associated with the stiffness and strength gains over the curing time provided by cementation need to be investigated, especially for tropical soils. Few studies investigated mixtures of tropical soils and high early strength Portland cement, in order to understand the changes in physical and mechanical properties associated with mineralogical and microstructural alterations caused by artificial cementation. This work aimed to study the effects of cementation on a tropical clay soil using ultrasonic method and to correlate the results with those of other tests. The ultrasonic pulse velocity (UPV) was evaluated for the natural soil and mixtures of soil with different cement contents (1%, 2%, 3%, 5%, 7%), after different curing times, based on propagation of longitudinal ultrasonic waves. Mineralogical and microstructural analyses, geotechnical characterization, resilient modulus (RM) and unconfined compressive strength (UCS) tests, and physical–chemical investigation through volumetric variation were also developed. The ultrasonic response revealed direct effects of cementation on micromorphology, plasticity and granulometry. A microstructure with larger pores was transformed into a dense structure with particles bonded by cementitious compounds. This change provided new paths for the propagation of ultrasonic waves (UPV increases exceeded fourfold for a cement content of 7%) and greater mechanical resistance to the application of cyclic and static loads. Nearly linear increases in UPV, UCS and RM were observed with the addition of cement. A good linear relationship was observed between the values of UPV and RM (R2 > 0.8968) or UCS (R2 > 0.8925).
Keywords: Curing time; Soil–cement mixtures; Stiffness; Strength; Ultrasonic pulse velocity